THE ROLE AND SIGNIFICANCE OF THE NEUROGYMNASTICS METHODOLOGY IN CORRECTIVE-DEVELOPMENTAL EDUCATION (Web of Teachers: Inderscience Research, 2026)
This article presents a scientific examination of the theoretical foundations, practical application, and effectiveness of the neurogymnastics — or "brain gym" — methodology in corrective-developmental education. The influence of cerebral hemisphere asymmetry and interhemispheric integration problems on the educational process is analyzed. The role of a movement exercise system, developed on the basis of Paul Dennison's methodology, in correcting speech and cognitive disorders is substantiated. The article also outlines the diagnostic indicators of interhemispheric dysfunction and the methodological principles of corrective intervention.